Level of Undernutrition and Its Determinants Among Children Aged 12–59 Months in Wolaita District, Ethiopia - Workie SB; Mekonen T; Fekadu W; Mekonen TC (Dove Medical Press, 2020)
Shimelash Bitew Workie,1 Tesfa Mekonen,2 Wubalem Fekadu,2 Tefera Chane Mekonen3 1College of Medicine and Health Sciences, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 3College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Shimelash Bitew Workie Email sbitew0@gmail.comBackground: Undernutrition remains one of the most common causes of morbidity and mortality among children throughout the world particularly in developing countries. The present study aimed to assess the magnitude and associated factors of undernutrition among children aged 12– 59 months.Methods: A community-based cross-sectional study was conducted in Wolaita district from May to June 2015. Multi-stage stratified systematic random sampling procedure was used. Data were collected using a pretested interviewer-administered questionnaire from 626 children aged 12– 59 months. Height and weight were measured by trained data collectors and WHO Anthro version 3.2.2 software was used. Data were entered into Epi Info version 3.3.5 and were exported and analyzed using SPSS version 21. Multivariable logistic regression model with a step-wise method was used to determine the predictors of undernutrition.Results: One third (34.1%; 95% CI 30.4– 37.9%) of children were stunted while 6.9% and 11.9% of them were wasted and underweight, respectively, based on WHO Z score <-2. Children live in mother-headed households which often use unprotected sources of water and children who did not get minimum dietary diversity were more likely to be stunted compared to their counterparts. Children residing in rural residences, being a male child, having less power for mother decision-making, presence of diarrhea in the last 2 weeks of the survey and who did not get the minimum dietary diversity were found to be significant determinants of underweight. Children living rural, male sex, their order of birth being 5th and above and who had not got the minimum meal frequency were more likely to be wasted than their counterparts. Conclusion and Recommendation: Undernutrition has a high prevalence in under-5-year-old children of Wolaita district. Under nutrition was associated with female-headed households, unprotected sources of water, below the minimum dietary diversity, rural residence, participation of mother in decision-making, presence of diarrhea, and minimum meal frequency. Thus, nutritional intervention programs in Wolaita district in Ethiopia should focus on these factors.Keywords: stunted, underweight, wasted, children, undernutrition, Ethiopia